2015
DOI: 10.1002/jmri.25054
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of pancreatobiliary-type from intestinal-type periampullary carcinomas using 3.0T MRI

Abstract: Progressive enhancement and low ADCmin values suggest a pancreatobiliary-type periampullary carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
(92 reference statements)
1
4
0
Order By: Relevance
“…In the present study, the ADC values of the IPACs were higher than those of the PPACs, which corresponded to the ADC quantitative analysis by Bi et al[16]. In their study, the mean ADC could not help differentiate these two histological groups, but ADC min achieved a significant difference ( P = 0.047; sensitivity, 85.2%; specificity, 50%; AUC = 0.672).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In the present study, the ADC values of the IPACs were higher than those of the PPACs, which corresponded to the ADC quantitative analysis by Bi et al[16]. In their study, the mean ADC could not help differentiate these two histological groups, but ADC min achieved a significant difference ( P = 0.047; sensitivity, 85.2%; specificity, 50%; AUC = 0.672).…”
Section: Discussionsupporting
confidence: 81%
“…A qualitative study found that the comprehensive evaluation of multiple CT features of the periampullary area could differentiate the histological subtypes, but required optimal duodenal distention and was highly dependent on the expertise of the radiologists[15]. An oval filling defect at the end of the bile duct on magnetic resonance cholangiopancreatography images tended to suggest IPAC but controversy still existed[16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity and specificity were found to be 91% and 59%, respectively, with a cut-off value of 1.50 x 10 -3 mm²/s. In their study, Bi et al [27] revealed that the average ADC was not able to differentiate these groups. However, they noticed that the ADCmin showed potential in terms of differentiating between the groups with a sensitivity of 85.2%, specificity of 50%, and an AUC of 0.672.…”
Section: Discussionmentioning
confidence: 90%
“…The novelty of our study arises from the fact that, to our knowledge, there are no other studies in the literature that performed volumetric histogram analysis in the paediatric HIE group. We evaluated only the ADC values derived from the b -value of 1000 mm 2 /s because no significant differences were found with low b -values in the studies carried out [ 26 , 27 ]. In our study, a retrospective analysis method with potential bias was used in patient selection.…”
Section: Discussionmentioning
confidence: 99%